Formulations of liposomal vaccine containing AdhO36 antigen and Î²-glucan as immunoadjuvant - Hidajah Rachmawati; Raditya Weka Nugraheni; Firasti Agung Nugrahening Sumadi; Helmy Yusuf (Pharmaciana, 2021)
Humans are the most crucial host of Salmonella Typhi as it has limited ability to reproduce outside the human body. Salmonella Typhi infections caused Typhoid fever which can be prevented with vaccines. This study aims to develop an effective typhoid fever oral vaccine using a liposomal delivery system. Â Several studies showed that the immunization of AdhO36 protein from Salmonella Typhi orally provides significant protection in inhibiting the Salmonella Typhi to the mice intestine. Î²-Glucan is a potent immunostimulant for macrophages activations. Meanwhile, the method used to produce Liposome formulations was using thin-film hydration. The liposomal products had good characteristics based on their particle size. The particle size results met the requirement for optimum intestinal absorption 399.220+28.095 nm Liposome+AdhO36 and 383.360+8.594 nm Liposome+Î²-glucan. Based on the zeta potential measurement, the electrical charges of the three formulations were positive, meaning that the liposome is cationic because of the DDAB (Dimethyl Dioctadecyl Ammonium Bromide) component. The positive charge will facilitate the internalization of antigen to the immunity cells.